ON SCALING OF SCHRÖDINGER EQUATION AND SOME RESULTS FOR HEAVY QUARKS MESONS - Fabiano, Nicola; Radenović, Stojan (Bulletin of Natural Sciences Research, 2021)
We consider the scaling of the Schrödinger equation in order to explicitly compute the energy density levels for a specific class of potentials. The resulting eigenvalues spectrum is compared to the heavy quarks mesons spectroscopy, showing at least for the heavier case _ an excellent agreement with the experimental data.
Keywords: Schrödinger equation; Semiclassical methods; Heavy quarks